1968
DOI: 10.1016/0028-3932(68)90036-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of discrimination training on pattern equivalence in monkeys with inferotemporal and lateral striate lesions

Abstract: Monkeys with inferotemporal (IT) lesions, monkeys with lateral striate (LS) lesions and unoperated controls discriminated between two patterns and were tested for pattern equivalence in three experiments. The 1T monkeys appeared to utilize salient cues more than control animals did and failed to identify specific pattern features (exps. 1 and 2). When the salient cues were removed (exp. 3) the IT animals gave evidence of normally identifying configurational cues. While two LS monkeys showed deficits like those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 17 publications
(24 reference statements)
2
17
0
Order By: Relevance
“…Thus, with the use of a mathematical stimulus sampling technique in analyzing data obtained in a multiple-choice experiment, resections of the inferotemporal cortex were shown to impair sampling when monkeys were trained to choose one of several objects (Pribram, 196Oa). A similar result was obtained when multiple features of a pattern were critical to performance (Butter, 1968). Furthermore, with the use of brain electrical responses, it was shown that recordings made from striate (visual projection) cortex reflected all of the feature characteristics of a briefly (50 msec) presented multifeatured stimulus.…”
supporting
confidence: 57%
“…Thus, with the use of a mathematical stimulus sampling technique in analyzing data obtained in a multiple-choice experiment, resections of the inferotemporal cortex were shown to impair sampling when monkeys were trained to choose one of several objects (Pribram, 196Oa). A similar result was obtained when multiple features of a pattern were critical to performance (Butter, 1968). Furthermore, with the use of brain electrical responses, it was shown that recordings made from striate (visual projection) cortex reflected all of the feature characteristics of a briefly (50 msec) presented multifeatured stimulus.…”
supporting
confidence: 57%
“…Not quite. In addition to impairments in color vision (Heywood et al, 1995), studies of equivalence behavior in which monkeys are trained with one class of stimuli and then tested with slightly altered versions of that same class have shown that monkeys with IT cortex lesions do not rely on the same cues for discriminating stimuli as normal animals do (Butter et al, 1965;Butter and Gekoski, 1966;Butter, 1968;Butter and Doehrman, 1968;Butter and Hirtzel, 1970;Iwai, 1985). It is possible, therefore, that the visual memory impairments that accompany IT cortex lesions might also be a product of disruptions in the processing of visual information.…”
Section: Levels Of Processing Failure?mentioning
confidence: 99%
“…Butter, Mishkin, and Rosvold (1965;Butter, 1968) found that after IT-lesioned monkeys had learned to discriminate a grating of a particular orientation and color from other patterns they were more likely than normals to inappropriately respond to stimuli of a similar orientation or color as the original rewarded stimulus. Analogous results obtain for the generalization of discriminations involving angles (Blake, Jarvis, & Mishkin, 1977).…”
Section: Lesion Studies In Animalsmentioning
confidence: 99%